Social Support and Hope Mediate the Relationship Between Gratitude and Depression Among Front-Line Medical Staff During the Pandemic of COVID-19 - Feng, Lijuan; Yin, Rong (Frontiers in Psychology, 2021)
Background The pandemic of Coronavirus Disease 2019 (COVID-19) has burdened an unprecedented psychological stress on the front-line medical staff, who are at high risk of depression. While existing studies and theories suggest that factors such as gratitude, social support, and hope play a role in the risk of depression, few studies have combined these factors to explore the relationship between them. Objective This study examined the mediating roles of social support and hope in the relationship between gratitude and depression among front-line medical staff during the pandemic of COVID-19. Methods This study used the Gratitude Questionnaire, the Perceived Social Support Scale (PSSS), the State Hope Scale (SHS), and the Center for Epidemiologic Studies Depression Scale to examine the gratitude, social support, hope, and depression among 344 front-line medical workers in Wuhan, which was the hardest-hit area of COVID-19 in China. Results The results showed that the prevalence of mild depressive disorder was 40.12% and the prevalence of major depressive disorder was 9.59% among front-line medical staff during the pandemic of COVID-19; gratitude has a direct and negative effect on depression. Gratitude was negative predictors of depression through the mediating variables of social support and hope [βgratitude–social support–depression = −0.096, 95%CI(−0.129 to −0.064); βgratitude–hope–depression = −0.034, 95%CI(−0.055 to −0.013)], as well as via an indirect path from social support to hope [βgratitude–social support–hope–depression = −0.089, 95%CI (−0.108 to −0.070)]. Conclusion The study findings indicate that gratitude as a positive emotion can reduce depression in medical staff by promoting social support and hope, respectively. Gratitude also reduced depression in health care workers through a chain mediating effect of social support and hope. Overall, gratitude can directly foster social support and hope, and protect people from stress and depression, which has implications for clinical interventions among front-line medical staff during the pandemic of COVID-19.